“The Role of Gender and Age in the Use of Emoji on Social Medai Among Millenials and Gen Z” - Helvira, Jenny; Geltri Sutra Purba; Ayudira; Honey Christine; Rani Syahfitri (Universitas Negeri Medan, 2024)
This study investigates the role of gender and age in emoji usage among Millennials and Generation Z, highlighting emojis as vital tools for conveying emotions and enhancing interpersonal connections on social media. Utilizing Gender and Language Theory and Digital Communication Theory, the research reveals that females use emotionally expressive emojis more frequently in personal contexts, while males favor neutral or humorous emojis for casual interactions. Additionally, Millennials tend to prefer positive and supportive emojis, reflecting a conventional communication style, whereas Generation Z exhibits a playful and creative approach, often employing emojis in subcultural contexts. These findings emphasize the complexity of emoji usage as reflections of social identities and relational dynamics, offering valuable insights for effective communication strategies in the evolving realm of digital interaction